Successful Event Management : a practical handbook - Shone, Anton; Parry, Bryn, 1961- (2019)
This title provides a guide to organising major events such as festivals, parties, concerts, weddings, and conferences. It includes photocopiable forms that will help readers to plan and budget, and case studies and websites to learn from.
Previous edition: 2013.
Includes bibliographical references and index.
Keywords: Special events -- Management; Customs and Folklore